KONSEP DAN PRAKTIK METODE PERIWAYATAN HADITS DAN TAKHRIJ AL-HADITS: Studi Terhadap Teks Hadits - Dozan, Wely; Sugitanata, Arif (Jurnal El-Hikam, 2021)
This paper attempts to discuss the concept and practice of the method of narrating hadith and takhrij al-hadith. Specifically, there are several aspects that become the focal point of this research, namely, First, looking back at the concept of the hadith narration method. Second, reveal how the concept of takhrij al-hadith. Third, give examples of practice in doing takhrij al-hadith. The research approach used is a literature study approach which is based on several supporting references related to books, journals, articles and so on. The results of this study indicate that the concept of narration of hadith is an activity of receiving and conveying hadiths, and relying on this hadith to a series of narrators using certain terms or symbols while takhrij hadith is a search or search for hadith as the original source of the hadith in question which is completely determined in the observations and the corresponding hadith sanad.